During the Migration Time: Oral History, Violence, and Identity in the Prehistoric Verde Valley. Issue 3 (2nd July 2016) - Guebard, Matthew C.
Abstract : Archaeological data supports Native American oral histories recounting violence, arson, and the abandonment of the Montezuma Castle (AZ O:5:14 [ASM]) and Castle A (AZ O:5:95 [ASM]) dwellings at the end of the fourteenth century. Oral histories provide context for this event by revealing larger patterns resulting in population emigration and the formation of cultural identities in the Verde Valley of central Arizona. The coordinated analysis of archaeological data and oral histories presented in this paper provide an accurate and insightful representation of past events and illustrate a strong connection between contemporary Native American communities and the archaeological sites at Montezuma Castle National Monument.